The Effect of Reciting the Qur’an with Makhraj on Saliva Volume and pH During Fasting - Sawitri Dwi Indah Pertami; Hesti Wira Ningsih; Nur Dianawati; Endah Kusumastuti; Dwi Leni Yuliana (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
An oral fluid called saliva contributes to the preservation of oral homeostasis. Both the major and minor salivary glands create saliva. Meanwhile, the practice of not eating or drinking is known as fasting. While fasting, saliva production is quite low, resulting from low stimulation to salivary glands. Salivary production, in fact, can be stimulated by mechanical stimuli, one of which is by reciting the Qur'an. Reciting the Qur'an with makhorijul huroof means reciting Qur'anic verses according to where the sound of the hijaiyah letters comes out. The resulting movement can stimulate the salivary glands and increase saliva production. The study, therefore, aims to determine the effect of reciting the Qur'an with makhraj on the volume and pH of saliva during fasting in Institut Ilmu Kesehatan Bhakti Wiyata Kediri students. This study employed a true experimental method with a pre-test-post-test control group design. The results data were analyzed and interpreted to test the hypothesis using the independent t-test with the variable data scale being ratio. The results revealed the significance value of the independent t-test on the difference between the pre-test and post-test data on volume and pH of the experimental group of 0.000 Asymp. Sig. (2-tailed). The p-value <0.05 indicates that there was a significant effect. This study concludes that reciting the Qur'an with makhraj can increase the volume and pH of saliva during fasting.